PENGARUH BRAND IMAGE DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA PELANGGAN HERO COFFEE SEMARANG - Alicia Victoria Salsabilla; Sudharto P Hadi; Ilham Ainuddin (Universitas Diponegoro, 2025)
Coffee shop is currently increasing making a tight competition. Supported by the lifestyle of people who often visit coffee shops. Hero Coffee Semarang is one of the coffee shop brands which in the last 5 years (2018 – 2022) has experienced fluctuating revenues and tends to decline. This could indicate a decrease in purchase decisions for Hero Coffee Semarang products. This research aims to determine the influence of brand image and social media marketing on purchase decisions of Hero Coffee Semarang customers. This type of research is explanatory research with a quantitative approach. The sampling technique uses accidental sampling and purposive sampling. The total sample was 97 respondents based on the sampling technique calculations proposed by Rao Purba (2006). Data collection techniques are through questionnaires and interviews, then the data obtained is continued at the processing stage using Smart PLS software version. This research results that brand image (X1) has a positive and significant effect on purchasing decisions (Y). Then, social media marketing (X2) has a positive and significant effect on purchasing decisions (Y). The brand image (X1) and social media marketing (X2) variables contributed 73.3% to purchasing decisions (Y). Based on the research results, researchers formulated suggestions for Hero Coffee, namely promotion with viral marketing, inviting food review influencers to increase popularity. Hero coffee needs to create iconic photo spots so that they can improve brand image, use social media advertisements and make the content more interesting and informative so that a large audience is reached and interested for the content. Hero Coffee along with consumers need to build discussions with consumers through social media comment columns, Google business reviews, or Instagram stories to make interactive. Suggestions for future research are to conduct longitudinal research and add variables such as service quality and café atmosphere.